Review Artikel: Evaluasi Mutu Fisik Sediaan Kapsul dalam Menjamin Kualitas Produk Farmasi - Elvira Silvany Zahara; Yasmine Eka Maulidya; Vira Maulidya; Helmalia Jelita Putri; Namira Salsabilah; Dewi Rahmawati; Yani Ambari; Dzakiyah Zhihrotulwillah (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Capsules are one of the most commonly used oral pharmaceutical dosage forms due to their ease of administration, ability to mask unpleasant tastes, and flexibility in formulation development. To ensure product quality, safety, and therapeutic effectiveness, capsule preparations must comply with physical quality requirements based on pharmacopoeial standards. This review article aims to analyze the physical quality evaluation parameters of capsule preparations in maintaining pharmaceutical product quality. The method used was a literature review of scientific articles obtained from databases such as Google Scholar, PubMed, and ScienceDirect, with publication years ranging from 2020 to 2026. From the collected literature, five relevant research articles were selected based on the focus of the study. The evaluation parameters discussed include granule flow properties, weight uniformity, disintegration time, and capsule content characteristics related to drug release. The results show that good granule flow properties affect the capsule filling process and weight consistency. In addition, disintegration time serves as an important parameter in determining the ability of capsules to release active ingredients. Capsule type and formulation composition, including HPMC-based enteric capsules, also influence drug release characteristics. Therefore, physical quality evaluation is essential to ensure the stability, quality, and therapeutic efficacy of capsule pharmaceutical products.